Ethnopolitical Entrepreneurship and the Political Role of Saxonness without Saxons in Sibiu - Monica Stroe (Sociologie Românească, 2011)
The paper discusses the symbolic capital of Saxonness in the Romanian and Transylvanian public sphere and its uses as a political and cultural resource. I am examining the historical representations of Saxonness and the local, national and European context in which they are activated and re-signified, acquiring contemporary meanings. I focus on the mechanisms behind the political support of Klaus Johannis, representative of The German Democratic Forum in Romania, the Saxon mayor of the city of Sibiu (Transylvania), currently serving his third four-year long mandate. My analysis will attempt to capture the relation between his noteworthy success as elected local representative and the apparently contradictory local demographic evolution: a Saxon minority whose numbers dropped severely in the last decades, reaching a lower limit of under 2% of the total local population. The study explores some of the possible mechanisms that lie at the foundation of the contemporary political capital of Saxonness in Sibiu, by focusing on the salience of ethnicity in elections media discourse and in the collective imagery as reflected in the Ethnobarometer, supported by historical arguments of the “myth of the Saxon”.